2018
DOI: 10.1063/1.5016245
|View full text |Cite
|
Sign up to set email alerts
|

Optical and electrical properties of the transparent conductor SrVO3 without long-range crystalline order

Abstract: It has been shown recently that the perovskite oxide SrVO3 is a transparent conductor with optical and electrical properties outreaching those of the most used material indium tin oxide (ITO). These properties, observed in the crystalline phase, imply the strong potential of SrVO3 for use as a lower cost alternative to ITO, but the possible integration of this perovskite oxide material in actual electronic devices is still an open question. One of the possible approaches for the integration of oxide materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 29 publications
3
45
0
Order By: Relevance
“…Thus, the observed evolution of the resistivity with T G can be explained by the decrease of disorder and therefore to the increase in crystalline quality, as was observed in the XRD study on LAO. However, for the films grown on LSAT, an exceptionally high crystalline quality is already observed at 400 °C, comparable to the one of the film grown at 700 °C, which does not seem consistent with structural disorder being at the origin of the degradation of the electronic transport. Moyer et al have shown that an imbalance of the Sr‐V stoichiometry may also be at the origin of high residual resistivities and low mobilities, but the RBS analysis of the films of this study did not show an evolution for different T G or different substrates.…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…Thus, the observed evolution of the resistivity with T G can be explained by the decrease of disorder and therefore to the increase in crystalline quality, as was observed in the XRD study on LAO. However, for the films grown on LSAT, an exceptionally high crystalline quality is already observed at 400 °C, comparable to the one of the film grown at 700 °C, which does not seem consistent with structural disorder being at the origin of the degradation of the electronic transport. Moyer et al have shown that an imbalance of the Sr‐V stoichiometry may also be at the origin of high residual resistivities and low mobilities, but the RBS analysis of the films of this study did not show an evolution for different T G or different substrates.…”
Section: Resultsmentioning
confidence: 70%
“…At most, we observe a variation in the resistivity of a factor of two. Hence, the influences of the substrate and T G are relatively small compared to the need of well‐defined crystalline perovskite structure for good transport properties, as was also pointed out for thin films on LSAT …”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations